Relações Entre Família E Escola A Partir De Uma Perspectiva Territorial Nos Municípios De Guarulhos E São Paulo Estudo De Caso Comparativo - Adao, Adalberto Dire [UNIFESP] (2017)
This study aims to identify and discuss across the some relations between Family and School, targeting the teaching and learning processes like convergence of this relations that mark the early years of elementary school, trying to understand yours manifestations across the territorial dimension of the your settings. The chosen path was a comparative case study between two schools from different municipal school systems, considering two movements. The first movement identifies and considers how families think the dwelling place, as well as weave expectations about the training offered by these institutions and the latter recognizes and raises questions about how teachers portray the place of professional practice and incorporate this reading their teaching practices. To this end we conducted interviews with teachers and students from families in the municipal two neighboring municipalities, in which through a semi-structured interview try to give voice to the research subjects, analyzing the data collected in order to establish a comparison between the realities presented, taking based on the arguments of the respondents. Families, schools, teachers and the place constituted object set of this investigation, since the processes of teaching and learning go beyond the school environment. With this study, we analyze a spectrum face constituting the processes of teaching and learning across the variables that permeate the school environment and the place of individuals in building their territoriality.